Adjunctive Therapy with Chinese Herbal Medicine Lowers Risk of Hearing Loss in Type 2 Diabetes Patients: Results from a Cohort-Based Case-Control Study - Hui-Ju Huang; Hanoch Livneh; Chieh-Tsung Yen; Ming-Chi Lu; Wei-Jen Chen; Tzung-Yi Tsai (MDPI AG, 2024)
Hearing loss is a frequently observed complication of type 2 diabetes (T2D). Emerging evidence has found that Chinese herbal medicine (CHM) can effectively treat chronic disease; nevertheless, it is unclear if adding CHM to the routine management of T2D would modify sequent risk of hearing loss. This cohort-based case-control study was conducted to address this issue. First, a total of 64,418 subjects aged 20-70 years, diagnosed with T2D between 2002 and 2011, were extracted from a nationwide health claims database. Among them, we identified 4516 cases of hearing loss after T2D by the end of 2013. They were then randomly matched to 9032 controls without hearing loss at a 1:2 ratio. Following conditional logistic regression, we found the addition of CHM to conventional care reduced the risk of developing hearing loss, with an adjusted odds ratio of 0.75 (95% confidence interval: 0.70-0.83). Specifically, taking CHM products for at least two years benefits T2D patients in lowering sequent risk of hearing loss. The findings herein implicated that integrating CHM into conventional care substantially correlated to lower risk of hearing loss for T2D patients, but further basic research is needed to secure the application of finished herbal products.